Formulation And Physical Quality Test Of Black Glutinous Rice (Oryza Sativa L. Var. Glutinosa) And Olive Oil Body Scrub - Herdianty, Juvita; Aniqoh Meliana Putri, Luluk; Wijayanto, Arif (Open Access Health Scientific Journal, 2025)
Background: The purpose of using a body scrub is to remove dead skin cells and dirt, and unclog pores, resulting in brighter, whiter skin. Many types of body scrubs are available today, each with a variety of benefits, from smoothing to whitening. Black glutinous rice is currently a popular choice for use in cosmetics. Black glutinous rice contains 109.52–256.61 mg of anthocyanin per 100 grams. The antioxidant activity of anthocyanins can be enhanced by the presence of other phytochemicals, such as flavanols, catechins, or vitamins, which are also commonly found in fruit.Methods: This research method is experimental in making body scrub preparations from black sticky rice as the active ingredient with varying concentrations of 5%, 10%, and 15%. Evaluation of the body scrub preparations by looking at the results of the physical quality of the preparations which include organoleptic tests, homogeneity tests, pH tests, adhesion tests, and spreadability tests. The body scrub preparations will be tested for 3 days and stored at room temperature. Data are analyzed descriptively by comparing them to the Indonesian National Standard.Results: The results of the study showed that the preparation met the physical quality requirements, the results of organoleptic quality, namely the formulation of body scrub preparations F1, F2, and F3. The results of the pH test of F1, F2, F3 were in the range of 6.03-6.48, the results of the spreadability test showed results in the range of 4.48-6.98, and the adhesion test produced a range of 0.2.30 -0.2.45.Conclusion: The conclusion of this study is that the formulations F1, F2 and F3 with the addition of olive oil have good physical quality, are stable and meet the Indonesian National Standard.